2018
DOI: 10.1159/000489156
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific Peptidase 22 Contributes to Colorectal Cancer Stemness and Chemoresistance via Wnt/β-Catenin Pathway

Abstract: Background/Aims: Two major barriers to the successful treatment of colorectal cancer (CRC) are the development of stem cell-like characteristics (stemness) and chemoresistance. Ubiquitin-specific peptidase 22 (USP22) is a deubiquitinating enzyme and putative CRC marker that has emerged as a potential cause of both phenomena in CRC. There is evidence that USP22 acts through the Wnt/β-catenin pathway and that downregulation of the latter may reduce chemoresistance. Methods: In this study, we used CRC tissue spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The 3'UTR of USP22 was predicted to be a binding site of miR‐30‐5p (Figure A). In our previous report, we found that USP22 plays an important role in CRC development . We therefore investigated whether USP22 is the target of miR‐30‐5p.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The 3'UTR of USP22 was predicted to be a binding site of miR‐30‐5p (Figure A). In our previous report, we found that USP22 plays an important role in CRC development . We therefore investigated whether USP22 is the target of miR‐30‐5p.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, we demonstrated that USP22 maintains stemness in CRC stem cells . To evaluate the effects of miR‐30‐5p on CRC cell stemness, we isolated CD133 + Caco2 and HCT15 cells using microbeads .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 The Wnt/β-catenin signalling pathway promotes cell proliferation and stem cell self-renewal. 36 Activation of the Wnt/β-catenin signalling pathway maintains stemness of breast cancer cells. 37 Thus, TCF7L2 mediates cell proliferation and stemness of breast cancer cells via the Wnt/β-catenin signalling pathway.…”
Section: Discussionmentioning
confidence: 99%